2016
DOI: 10.12945/j.aorta.2016.15.001
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Outflow Tract Pseudoaneurysm after Aortic Valve Replacement

Abstract: Left ventricular outflow tract pseudoaneurysm is an uncommon complication following aortic valve replacement (AVR), occurring most frequently secondary to endocarditis. We present a case of a 47-year-old female with a history of intravenous drug abuse and a past surgical history of two AVRs (2001 and 2009 with aortic root replacement for endocarditis) who presented with symptoms of lower extremity weakness. Subsequent radiologic imaging revealed the presence of a left ventricular outflow tract pseudoaneurysm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…High flows in the LVOT cause further stress, as blood enters the surrounding mediastinum, forming a contained paravalvular leak. 9 One case-control series in patients without endocarditis showed that the implantation of composite grafts increases the risk for pseudoaneurysm compared with aortic valve replacement alone, though all pseudoaneurysms developed in this series were in the aortic root and ascending aorta, rather than the LVOT. 10 Our patient did not have prior infective endocarditis but was immunocompromised.…”
Section: Discussionmentioning
confidence: 70%
“…High flows in the LVOT cause further stress, as blood enters the surrounding mediastinum, forming a contained paravalvular leak. 9 One case-control series in patients without endocarditis showed that the implantation of composite grafts increases the risk for pseudoaneurysm compared with aortic valve replacement alone, though all pseudoaneurysms developed in this series were in the aortic root and ascending aorta, rather than the LVOT. 10 Our patient did not have prior infective endocarditis but was immunocompromised.…”
Section: Discussionmentioning
confidence: 70%
“…Our patient presented with a rare case of mycotic pseudoaneurysm due to persistent MRSA bacteremia, and mechanical valve endocarditis. Risk factors for pseudoaneurysm formation in this case included previous aortic valve and ascending aortic reconstruction, trauma, and endocarditis with persistent bacteremia 2,3 . If left untreated, such a pseudoaneurysm is at risk for rupture, tamponade, hemorrhagic shock, and sudden death 4 .…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports have described pseudoaneurysm after multiple aortic valve replacements, 3 after anastomotic dehiscence, 4 graft deterioration, 5 traumatic disruptions, 6 isolated coronary button pseudoaneurysm repairs, 7 or full root replacement using Cabrol-type reimplantation 8 ; however, this patient had already undergone 3 prior operations, including Cabrol-type reimplantation of the RCA and presented the additional challenges of LM stenting and a mechanical valve also in the mitral position.…”
Section: Commentmentioning
confidence: 86%